PARTISIPASI POLITIK MASYARAKAT PADA PILKADA KOTA PEKANBARU TAHUN 2017 - Fadil Anugrah Prasetyo; Fitriyah . (Journal of Politic and Government Studies, 2018)
Participation in politics is a vital aspect in a fabric of democracy, as well as are the hallmark of the modernization of politics. As the process of transformation of politics, the meaning of the election besides being a part of the arrangement of the power structure of the central bank to ensure does it do the mechanism of checks and balances between political institutions of the central level to the area, people expect also that elections can produce regional heads who are accountable, quality, legitimate, and sensitive to the public interest. This study aims to determine the factors that affect the political participation of society in local elections in the city of Pekanbaru year 2017. This study using the kind of research ekspanatori with quantitative. The samples used in this study is a multistage random sampling by using the data from questionnaires. The response of the Pekanbaru City in the election in 2017 can be concluded in participating, you know Rational is an influential factor in political participation of the city of Pekanbaru. Based on the results of the processing and analysis of data that has been raised in the calculation of coefficient of the correlation to the Working Group on the Commission has a positive value to political participation. This means that the higher the Working Group on the Commission the higher the relationship in the Participation of the city of Pekanbaru.The results of the conclusions in this study based on the results of processing and analyzing the data that has been stated in the calculation of the correlation coefficient of Sociological Factors there is no significant relationship with Community Political Participation in Pekanbaru City Election. Psychological factors have a significant relationship with Community Political Participation in Pekanbaru City Election. Rational Factors have a significant relationship with Community Political Participation in Pekanbaru City Election. The DPT Administration factor has a significant relationship with the Community Political Participation in the Pekanbaru City Election. The Working Factors of KPU have a significant relationship with Community Political Participation in Pekanbaru City Election. Working Factors Candidates have a significant relationship with Community Political Participation in Pekanbaru City Election.Key words: Political Participation, Elections